Reaction to Dominiak and Wysocki on Evictionism and Abortion - Block, Walter (Studia z Historii Filozofii, 2025)
Dominiak and Wysocki are willing to stipulate, arguendo only, that the unwanted fetus is a trespasser. That is a major claim of mine in this intellectual battle I have been having with these two authors. So I greatly appreciate their attempt to show that my evictionist thesis should “still be rejected as either unlibertarian or redundant” even under conditions very favorable to my own view. Nonetheless, I persist in my proposition despite the very thorough, intelligent, reasonable, well thought out criticism they make of it.